2018
DOI: 10.4103/ijmy.ijmy_66_18
|View full text |Cite
|
Sign up to set email alerts
|

Perception toward the disease of the people affected by leprosy

Abstract: The present study emphasizes the need for continuous counseling and health education for persons affected with leprosy to avoid or minimize the psychological problems. Periodical screening and counseling will improve their psychosocial well-being and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 0 publications
0
10
0
12
Order By: Relevance
“…A maior parte dos entrevistados relataram problemas de cunho psicológico (Xiong et al, 2019). Já o estudo 6 identificou que 60% dos estudados eram homens, com até 45 anos, 55% eram trabalhadores braçais com renda familiar mensal menor que 5000 mil reais (Govindharaj et al, 2018).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A maior parte dos entrevistados relataram problemas de cunho psicológico (Xiong et al, 2019). Já o estudo 6 identificou que 60% dos estudados eram homens, com até 45 anos, 55% eram trabalhadores braçais com renda familiar mensal menor que 5000 mil reais (Govindharaj et al, 2018).…”
Section: Resultsunclassified
“…O artigo 6 identifica que mais da metade da população da pesquisa possui deficiência física (Govindharaj et al, 2018).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Patients with leprosy suffer several biological and psychosocial consequences (4)(5)(6) . In spite of the disease been characterized by skin problems and sensorimotor disorders, studies point to a larger range of involvement (7)(8)(9) . Recent publications showed that patients with leprosy have limitations in performing activities of daily living (ADL), and a great susceptibility to physical disabilities and morbidities (10)(11)(12) .…”
Section: Introductionmentioning
confidence: 99%
“…Peters et al (2014) observed that the women who had concealed their illnesses were the ones who most frequently reported feelings of fear, sadness, shame, low self-esteem and depression, and that these feelings often resulted in self-isolation. Besides, women affected by leprosy experience more fear of the disease than the men affected by leprosy (Govindharaj et al, 2018). Out of fear of infecting family members, affected women keep themselves aloof and are constantly worried about their marriage prospects or, if married, about divorce and separation.…”
Section: Introductionmentioning
confidence: 99%